Análisis Financiero a la “Cooperativa de Ahorro y Crédito de la Cámara de Comercio de Macará CADECOM” del cantón Macará provincia de Loja, periodo 2021-2022 - Quezada Tamayo, Erika Nayeli (2024)
The present study, titled "Financial Analysis of the (CADECOM) COOPERATIVA DE AHORRO Y CREDITO DE LA CÁMARA DE COMERCIO DE MACARÁ, Province of Loja, for the Period 2021-2022," provides an in-depth examination of the cooperative's financial condition over the specified period. To achieve the objectives set forth, a comprehensive financial analysis was conducted to understand the cooperative’s economic and financial status through both horizontal and vertical analysis, as well as to assess financial performance using the CAMELS indicators established by the Superintendency of Popular and Solidarity Economy. The methodology included a review and analysis of CADECOM’s financial statements using techniques such as interviews, observation, bibliographic research, and document review. The following methods were also employed: the scientific method provided a logical understanding of each process involved in the financial evaluation, allowing for correlation between theory and practice; the inductive method enabled a specific understanding of the entity's information, while the deductive method facilitated a theoretical review to find relevant information for the entity’s economic analysis; and the analytical and mathematical methods were applied in vertical and horizontal analysis to examine and understand the causes of variations within the entity. Finally, the statistical method was used with pivot tables to manage quantitative data, along with the application of financial indicators relevant to the cooperative’s segment, ultimately allowing for the results to be presented to the cooperative. As findings for the evaluated period, the CADECOM COOPERATIVA DE AHORRO Y CREDITO DE LA CÁMARA DE COMERCIO DE MACARÁ demonstrated financial growth in both assets and liabilities, along with an increase in equity, indicating a positive trend in the entity's financial health. In conclusion, through the review of its financial statement trends and the use of key indicators, it was determined that, while the cooperative has managed to maintain adequate liquidity and reduced delinquency levels in its credit portfolio, it faces significant challenges in terms of profitability and operational efficiency. Addressing these challenges will be essential to improve its performance and ensure greater financial stability in the long term.